Chemisorption of exchange-coupled [Ni2L(dppba)]+ complexes on gold by using ambidentate 4-(Diphenylphosphino)benzoate co-ligands - Golecki, Matthias; Lach, Jochen; Jeremies, Alexander; Lungwitz, Frank; Fronk, Michael; Salvan, Georgeta; Zahn, Dietrich R. T.; Park, Jaena; Krupskaya, Yulia; Kataev, Vladislav; Klingeler, Rüdiger; Büchner, Bernd; et al. (Chemistry - a European journal, 2013)
A new strategy for the fixation of redox-active dinickel(II) complexes with high-spin ground states to gold surfaces was developed. The dinickel(II) complex [Ni2L(Cl)]ClO4 (1ClO4), in which L2− represents a 24-membered macrocyclic hexaaza-dithiophenolate ligand, reacts with ambidentate 4-(diphenylphosphino)benzoate (dppba) to form the carboxylato-bridged complex [Ni2L(dppba)]+, which can be isolated as an air-stable perchlorate [Ni2L(dppba)]ClO4 (2ClO4) or tetraphenylborate [Ni2L(dppba)]BPh4 (2BPh4) salt. The auration of 2ClO4 was probed on a molecular level, by reaction with AuCl, which leads to the monoaurated NiII2AuI complex [NiII2L(dppba)AuICl]ClO4 (3ClO4). Metathesis of 3ClO4 with NaBPh4 produces [NiII2L(dppba)AuIPh]BPh4 (4BPh4), in which the Cl− is replaced by a Ph− group. The complexes were fully characterized by ESI mass spectrometry, IR and UV/Vis spectroscopy, X-ray crystallography (2BPh4 and 4BPh4), cyclic voltammetry, SQUID magnetometry and HF-ESR spectroscopy. Temperature-dependent magnetic susceptibility measurements reveal a ferromagnetic coupling J=+15.9 and +17.9 cm−1 between the two NiII ions in 2ClO4 and 4BPh4 (H=−2 JS1S2). HF-ESR measurements yield a negative axial magnetic anisotropy (D<0), which implies a bistable (easy axis) magnetic ground state. The binding of the [Ni2L(dppba)]ClO4 complex to gold was ascertained by four complementary surface analytical methods: contact angle measurements, atomic-force microscopy, X-ray photoelectron spectroscopy, and spectroscopic ellipsometry. The results indicate that the complexes are attached to the Au surface through coordinative AuP bonds in a monolayer.
Gesehen am 17.02.2020
Im Titel ist die Zahl "2" tiefgestellt und das Pluszeichen hochgestellt